PENERAPAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN KERJA SAMA DAN PRESTASI BELAJAR MATEMATIKA - Subhansyah (UNIB Press, 2022)
This study aims to describe the application of the PMRI approach can improve cooperation and student achievement in Mathematics for VII grades at MTs Negeri 1 Pagar Alam. In addition, to describe the effectiveness of implementing the PMRI approach if compared to conventional learning methods. The type of research is Penelitian Tindakan Kelas (PTK) with 4 phase, namely Action Planning, Action Implementation, Observation and Reflection. This research was done in 3 cycles, namely Cycle I, Cycle II and Cycle III. The population in this study amount 190 students of VII grade at MTs Negeri 1 Pagar Alam. This research using total sampling method by making the entire population into a sample. 26 students of VII grade at MTs Negeri 1 Pagar Alam acts as an action class. Data collection techniques using observation sheets and tests. Based on observations from the observers, there was an increase in each cycle starting from cycle I, cycle II and cycle III both in aspects of teacher learning activities and aspects of student cooperation. This research concluded that the application of the PMRI approach can improve cooperation and learning achievement of VII grade students at MTs Negeri 1 Pagar Alam